TechWare: Spoken Language Understanding (SLU) Resources - Tur, Gokhan; Wang, Ye-Yi; Hakkani-Tür, Dilek (IEEE Signal Processing Magazine, 2013)
This column first presents a very high level review of the SLU technology, starting from its place in a spoken dialog system, then focusing on well established SLU tasks such as domain detection, intent determination, and slot filling, along with corresponding benchmark data sets and methods.